Absorption properties of a multilayer composite nanoparticle for solar thermal utilization. (June 2022) - Gong, Han; Shao, Wei; Ma, Xiaoteng; Cui, Zheng
Highlights: A new Ag-SiO2 -Ag cylindrical nanoparticle is proposed. The nanoparticle is tuned to enhance solar absorption. Widening the absorption band by electroresonance and magnetic resonance. The nanoparticle can excite three absorption peaks in 390 nm, 470 nm and 780 nm. The maximum absorption peak of the nanoparticle is 2.28 times that of the silver nanoparticle. Abstract: As the primary way of solar thermal utilization, direct absorption solar collector (DASC) is attracting widespread attention. Nanofluids have good development prospects in DASC due to their excellent absorption and heat transfer properties. In this study, a three-layer cylindrical Ag-SiO2 -Ag composite nanoparticle is proposed. The advantages of Ag-SiO2 -Ag nanoparticle are proved by comparing the absorption performance with other materials and the same structure of sterling silver. The maximum absorption peak of the nanoparticle is 2.28 times that of the silver nanoparticle. At the same time, the influence of the size parameters of composite nanoparticle on the absorption performance is also discussed, which has an important reference value for the sensitive tuning of composite nanoparticle in different scenarios. Finally, the reasons for the enhanced absorption performance of the composite nanoparticle are revealed by analyzing the electromagnetic field distribution around the nanoparticle. The composite nanoparticle makes full use of various electrical and magnetic resonance modes to excite the three absorption peaks in 390 nm, 470 nm and 780 nm, thus improving the absorption performance of the nanoparticle. The composite nanoparticle proposed has positive significance for promoting the development of high-performance DASC.